Aplikasi Mobile Pawmatch untuk Pencarian Pasangan Kucing dan Anjing - Siti Julianingsih Nurfitriyani (Jurnal Kajian Ilmiah, 2024)
This research aims to design a mobile-based application called Pawmatch which is used to find partners for ats or dogs. This application can be used by dog or cat owners to bring together pets that are in heat and are not sterilized so they can mate. By utilizing the services in this application, it is hoped that cat or dog owners will have no difficulty in mating their pets while also being able to produce good and suitable cat or dog offspring as desired. Cat or dog owners who want to use this application must register by filling in the owner and pet information which can later be seen in the application as a reference for finding a pet partner that suits the type of animal and the owner's wishes. This application will be connected to The Cat Fanciers' Association (CFA) and Perkumpulan Kinologi Indonesia (PERKIN) to validate cat pedigree certificate numbers and dog stamp certificates entered by pet owners. Apart from that, this application will also implement a Global Positioning System (GPS), so that when a cat or dog owner searches for a partner for their pet, the search results can be adjusted to the location of the cat or dog owner. The design of this application was carried out by applying the Unified Modeling Language (UML) method.